PENGARUH LINGKUNGAN KERJA FISIK TERHADAP PRODUKTIVITAS KERJA KARYAWAN OPERATOR BAGIAN PRODUKSIPADA PERUSAHAAN MANUFAKTUR DI PT ABC BATAM - Wahyu Ningrum Handayani; Shinta Wahyu Hati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
The purpose of this study is to determine the extent to which the influence of the physical work environment on employee productivity. The type of research used is quantitative research with explanatory research approach. The sample of the research is the operator part workers in the Manufacturing Company. The analytical method used is Multiple Linear Regression using SPSS version 20. The results showed from the five factors related to the physical work environment ie Temperature Variables, Noise, Vibration, Lighting, and air circulation indicate that the five variables have an effect on employee productivity